Hyperintense Optic Nerve due to Diffusion Restriction: Diffusion-Weighted Imaging in Traumatic Optic Neuropathy - Bodanapally, U.K. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Abnormal signal intensity of the optic nerve due to diffusion restriction may be seen in traumatic optic neuropathy. In addition to evaluating optic nerve hyperintensity on diffusion-weighted imaging, we compared the group differences of ADC values between the injured and uninjured contralateral nerve and identified the relation between measured ADC values and admission visual acuity. MATERIALS AND METHODS: We retrospectively evaluated 29 patients with traumatic optic neuropathy who underwent MR imaging with DWI. Uninjured contralateral optic nerves were used as controls. Two attending radiologists, blinded to the side of injury, independently reviewed the DWI for the presence of signal-intensity abnormality and obtained ADC values after manually selecting the ROI. RESULTS: Hyperintensity of the optic nerve was demonstrated in 8 of the 29 patients, with a sensitivity of 27.6% (95% CI, 12.8–47.2) and a specificity of 100% (95% CI, 87.9–100). ADC values were obtained in 25 patients. The mean ADC in the posterior segment of the injured nerve was significantly lower than that in the contralateral uninjured nerve (Welch ANOVA, F = 9.7, P = .003). There was a moderate-to-strong correlation between low ADC values and poor visual acuity in 10 patients in whom visual acuity could be obtained at admission (R = 0.7, P = .02). Patients with optic nerve hyperintensity presented with worse visual acuity. CONCLUSIONS: Hyperintensity of the optic nerve due to diffusion restriction can serve as a specific imaging marker of traumatic optic neuropathy. When paired with reduced ADC values, this finding may be an important surrogate for visual acuity.